1983
DOI: 10.1038/303808a0
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the T3-associated 90K heterodimer as the T-cell antigen receptor

Abstract: Several surface molecules appear to be involved in antigen recognition by human T lymphocytes including the monomorphic 20/25K T3 structure present on all mature T lymphocytes and the subset-specific associative recognition elements, T4 and T8 (refs 1-8). More recently, Ti1, a clonally unique antigen recognition structure comprised of a 49,000 molecular weight (49K) alpha-chain and a 43K beta-chain, linked to T3 was identified on a major histocompatibility complex (MHC) class I specific T8+ T-cell clone, CT8II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
227
2

Year Published

1984
1984
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 493 publications
(243 citation statements)
references
References 17 publications
13
227
2
Order By: Relevance
“…Biochemically, the clonotypic receptor consists of two disulphide-linked chains, a basic β chain and an acidic α chain, both of which have a molecular weight between 40 and 50 kd [33][34][35]. By peptide mapping, these chains differ from each other and appear to have variable and constant sequence properties [34,36].…”
Section: The T-cell Receptor For Antigen and Mhc Proteinsmentioning
confidence: 99%
“…Biochemically, the clonotypic receptor consists of two disulphide-linked chains, a basic β chain and an acidic α chain, both of which have a molecular weight between 40 and 50 kd [33][34][35]. By peptide mapping, these chains differ from each other and appear to have variable and constant sequence properties [34,36].…”
Section: The T-cell Receptor For Antigen and Mhc Proteinsmentioning
confidence: 99%
“…Most nature, CD3-bearing peripheral blood T cells have a heterodimeric T-cell antigen receptor (TCR) composed of a and ,B chains (1)(2)(3)(4). However, T cells appearing early in thymic ontogeny and dendritic epidermal cells display an alternative heterodimeric TCR, consisting of y and 8 chains, in association with the CD3 molecule (5)(6)(7)(8).…”
mentioning
confidence: 99%
“…This direct mitogenic action is only found at high antibody cell ratlos it has practicaliy vamshed already at the fourfold higher dilution of 9 3 mAb (Table 4) whtre is thc enhancemeni of growth piomoting Signals is deteeted even at η g/ml 9 3 mAb [5] It may be concluded that the mitogenic action of 9 3 mAb depends on the prestnee of monocytes and is quenched by HS Α likely cause of the suppression of the mitogenic action in media supplemcnted by HS is their relativcly high content in human immunoglobulm molecules It might then be proposed that the binding of 9 3 mAb to Fc reeeptors of monocytes and as a consequence the possibie clustering of 190/44 is function dlly important This hypothesis is further supported by the recently reported finding that F(ab) 2 but not l· h fragments of 9 3 mAb have functional tffects on Γ cclls [17] Howevtr it cannot be exeluded that the quenching by IIS is at least in part due to thc presence of matenal which reacts with 9 3 mAb (e g shed T90/44) [5] 3.5 Γ90/44 expression is mduced in activated Γ cells…”
Section: Lymphocyte Transformation Testsmentioning
confidence: 77%